Conclusions and Outlook - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
There are a number of investigations and tests to determine the quality and reliability of the insulation material. Crucial criteria in these tasks are the detection, localization, and evaluation of partial discharges (PDs). PDs are partial breakdowns in insulation materials, surface discharges on insulators, or discharges in gases on tips or edges of conductive parts. Recently, PD behavior under alternating voltage stress has been researched and applied, and PD behavior under stress of direct voltage has become the focus of interest due to the increasing use of direct current (DC) transmission. Due to the greater need for transmission and use of direct voltage, the effect of such voltage stress on systems and apparatus is of substantial interest. The direct voltage (DC) PD phenomena must be clearly understood since these phenomena are entirely different from the alternating voltage (AC) PDs. Unfortunately, the direct voltage PD phenomena have not yet been fundamentally researched.
Keywords: Alternating current; High Voltage; High voltage insulation and dielectric phenomena